2020
DOI: 10.31557/apjcp.2020.21.10.3027
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Low HER2/neu Expression on the Clinicopathological Characteristics of Triple-Negative Breast Cancer Patients

Abstract: Background: Triple-negative breast cancer (TNBC) is an aggressive type of breast cancer (BC), and its diagnosis is associated with negative expression of hormone receptors and HER2/neu. It consists of 10-20% of all BCs diagnosed. Methods and materials: This study focuses on three groups with different pathology: group one showed complete triple-negative HER2 expression with IHC of BC; groups two and three included patients with ER-, PR-, and HER2 1+ , and ER-, PR-, and HER2 2+ with a negative FISH test. These … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 24 publications
4
13
0
Order By: Relevance
“…Consistent with most previous studies, this study found that tumors with HER2-low expression were more likely to be HR-positive and invasive ductal adenocarcinoma 14 , 17 – 19 . In addition, the results showed that HER2-low breast cancers had lower tumor grades and fewer visceral metastases.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Consistent with most previous studies, this study found that tumors with HER2-low expression were more likely to be HR-positive and invasive ductal adenocarcinoma 14 , 17 – 19 . In addition, the results showed that HER2-low breast cancers had lower tumor grades and fewer visceral metastases.…”
Section: Discussionsupporting
confidence: 92%
“…Interestingly, they did not find a similar association in HR-negative breast cancers 17 . In contrast, Dehghani et al found that HER2 IHC2+/ISH negative tumors had less lymphovascular invasion and fewer basal-like subtypes than HER2-zero tumors in triple-negative breast cancers 14 . Due to the limitation of the NCDB dataset, we could not provide detailed molecular data such as KI-67, or genomic data of the metastatic HER-2 low tumors in this study.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…To date, robust studies focusing on HER2-low breast cancer in China are lacking. Few studies from western countries combining HER2-low breast cancer patients from different datasets or clinical trials have yielded varying results (14)(15)(16). In this study, we aimed to characterize the clinicopathological features, survival, and prognosis of HER2-low tumors in metastatic breast cancer (MBC) based on the China National Cancer Center database and compare with HER2-zero tumors.…”
Section: Introductionmentioning
confidence: 99%
“…survived longer in the overall population and HR + subgroup [14]. Another study by Dehgani et al in TNBC obtained a similar result: patients with HER2 2 + had a lower rate of recurrence and longer overall survival (OS) [23]. In addition, other studies found no statistically signi cant difference in OS between patients with HER2-low and HER2-zero tumors [12,19].…”
Section: In Regard To Prognosis Previous Studies Have Shown Different...mentioning
confidence: 73%